POLITICS OF BIOPIRACY: AN ADVENTURE INTO HOODIA/XHOBA PATENTING IN SOUTHERN AFRICA - Amusan, Lere (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Africa is being described as the wretched of the earth, despite this, the continent is endowed with natural resources, dynamic ecosystem, and different species of plants and animals, and species derivatives. This paper area of departure is to focus on Hoodia, a plant that is being a source of food, medicine and water for the San and Khoe indigenous peoples before the advent of Europeans into southern Africa. South African Council for Scientific and Industrial Research (CSIR) dubiously patented Hoodia without observing the basic indices of geographical indications (GIs), indigenous knowledge (IK), novelty, access sharing benefit (ASB), prior informed consent (PIC) and sustainability of ecosystem before the rights was sold to Phytopharm pharmaceutical company. Materials and methods: This article adopts neoliberal thesis with emphasis on complex interdependence theory of organic linkages between developing and developed countries. Secondary sources of information taken into account of qualitative and critical discuss content analyses dominate this paper. Result: The paper recommends a linkage between developed and developing states based on endowment theory and comparative advantage with the notion of adhering to the Convention on Biological Diversity (CBD) which has three objectives: the conservation of biodiversity; the sustainable utilisation of indigenous biological resources (IBR); and fair and equitable benefit sharing. Conclusion: The paper recommends that there is a need to follow CBD and other relevant international regimes that promote equal exchange in exploitation of Africa resources as against the present skewed arrangement that is in favour of multinational corporations (MNCs).